The Role of Speech-Specific Properties of the Background in the Irrelevant Sound Effect. Issue 3 (March 2014) - Viswanathan, Navin; Dorsi, Josh; George, Stephanie
The irrelevant sound effect (ISE) is the finding that serial recall performance is impaired under complex auditory backgrounds such as speech as compared to white noise or silence. Several findings have demonstrated that ISE occurs with nonspeech backgrounds and that the changing-state complexity of the background stimuli is critical to ISE. In a pair of experiments, we investigate whether speech-like qualities of the irrelevant background have an effect beyond their changing-state complexity. We do so by using two kinds of transformations of speech with identical changing-state complexity: one kind that preserved speech-like information (sinewave speech and fully reversed sinewave speech) and others in which this information was distorted (two selectively reversed sinewave speech conditions). Our results indicate that even when changing-state complexity is held constant, sinewave speech conditions in which speech-like interformant relationships are disrupted, produce less ISE than those in which these relationships are preserved. This indicates that speech-like properties of the background are important beyond their changing-state complexity for ISE.